Current understanding of CTLA-4: from mechanism to autoimmune diseases - Hossen, Md Munnaf; Ma, Yanmei; Yin, Zhihua; Xia, Yuhao; Du, Jing; Huang, Jim Yi; Huang, Jennifer Jin; Zou, Linghua; Ye, Zhizhong; Huang, Zhong (Frontiers in Immunology, 2023)
Autoimmune diseases (ADs) are characterized by the production of autoreactive lymphocytes, immune responses to self-antigens, and inflammation in related tissues and organs. Cytotoxic T-lymphocyte antigen 4 (CTLA-4) is majorly expressed in activated T cells and works as a critical regulator in the inflammatory response. In this review, we first describe the structure, expression, and how the signaling pathways of CTLA-4 participate in reducing effector T cell activity and enhancing the immunomodulatory ability of regulatory T (Treg) cells to reduce immune response, maintain immune homeostasis, and maintain autoimmune silence. We then focused on the correlation between CTLA-4 and different ADs and how this molecule regulates the immune activity of the diseases and inhibits the onset, progression, and pathology of various ADs.Finally, we summarize the current progress of CTLA-4 as a therapeutic target for various ADs.